Negative Influence of Alcohol Drink on Driver Work Activity - Хонсаидов Мухсинали Махаммадалиевич (European Science Publishing, 2023)
This article extensively covers the issues of morality, decency, which are considered one of the most important qualities of a person's life simultaneously with the negative impact of alcohol on the driver's working life and factors that slow down the normative working capacity of the human body.
Keywords: driver, alcohol, drugs, vodka, inclination, degree, ethics, morality, social, cruelty.